2016
DOI: 10.4103/0300-1652.182074
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum uric acid, urinary albumin excretion, and glycated hemoglobin in Type 2 diabetic patient

Abstract: Background:Diabetes mellitus (DM) is a chronic disease characterized by insulin deficiency or peripheral resistance resulting in hyperglycemia. Poor glycemic control leads to diabetic complications. Hyperuricemia has been reported with increased risk of renal insufficiency. The aim of this study was to evaluate the relationship between serum uric acid concentration, degree of urinary albumin excretion (UAE) and glycated hemoglobin (HbA1c) in Type 2 DM (T2DM) patients.Materials and Methods:Serum uric acid conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Multiple regression analysis was done which showed that serum uric acid concentration, systolic blood pressure, HbA1c and total duration of DM were independent determinants of UAE. 16 Another study done by Suryawanshi and associates showed a positive association between urine microalbumin and levels of uric acid in serum (p<0.001), hence concluded that the levels of uric acid in serum and urine microalbumin were early diagnostic markers for kidney and atherogenic cardiovascular diseases, besides this, it was also very helpful in defining the prognostic monitoring of the disease in Type-2 diabetics. 17…”
Section: Discussionmentioning
confidence: 94%
“…Multiple regression analysis was done which showed that serum uric acid concentration, systolic blood pressure, HbA1c and total duration of DM were independent determinants of UAE. 16 Another study done by Suryawanshi and associates showed a positive association between urine microalbumin and levels of uric acid in serum (p<0.001), hence concluded that the levels of uric acid in serum and urine microalbumin were early diagnostic markers for kidney and atherogenic cardiovascular diseases, besides this, it was also very helpful in defining the prognostic monitoring of the disease in Type-2 diabetics. 17…”
Section: Discussionmentioning
confidence: 94%
“…One study finds that TC and abnormal LDL-C values of patients with HbA1c ≥7.0% were significantly higher than those of patients with HbA1c <7.0% [ 32 ]. At the same time, studies on patients with type 2 diabetes have found that serum uric acid concentration is associated with microalbuminuria and glycosylated hemoglobin [ 33 ]. These results are consistent with our results, and our study further found that the risk of elevated HbA1c increased by 10.2% for each unit of TG and decreased by 48.0% for each unit of HDLC.…”
Section: Discussionmentioning
confidence: 99%
“…Other variables in this study included age (years), gender (male/female), race (Mexican American/other Hispanic/non-Hispanic white/non-Hispanic black/other race), the ratio of household income to poverty, an education level (lower than high school/high school or general education development/high school and above), body mass index (BMI, kg/m 2 , calculated as body weight (kg) divided by the square of height (m)), energy and nutrition intake in the diet, blood pressure level (systolic blood pressure and diastolic blood pressure), renal function level (urinary albumin, urinary creatinine and urinary albumin creatinine ratio), blood lipid level (low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, triglyceride, and total cholesterol), smoking status (whether or not to smoke at least 100 cigarettes in a lifetime), and drinking status (once drinking 4/5 and more sitting time per day). The criteria for selecting covariates are based on previously published studies and variables [ 3 , 7 ]. The data used in this study can be found on the NHANES website.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that SUA was closely related to HbA1c and urinary microalbumin in diabetic patients. It was essential for diabetic patients to check HbA1c levels regularly and prevent renal damage [ 3 ]. A retrospective study in China found that SUA was positively correlated with hyperinsulinemia and insulin resistance in prediabetic patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%